Thermoplastic optical material polymer as well as preparation method and application thereof
By using specific isocyanates, sulfur-containing compounds and hydroxy monomers in polyurethane optical materials, thermoplastic optical material polymers containing Class I and Class II structures are prepared, which solves the problems of uncontrollable reactions and poor processing performance, and achieves the optimization of controllable reactions and processing performance.
Patent Information
- Application Number
- CN202411918708.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The problems of uncontrollable reactions of existing polyurethane optical materials, poor processing performance, easy decomposition and insufficient toughness during the preparation process.
A thermoplastic optical material polymer is obtained by using specific isocyanate and sulfur-containing compounds and adding hydroxy monomers. This material contains Class I structure and Class II structure, and the peak-area ratio controllable reaction and optimization of processing performance through the nuclear magnetic resonance hydrogen spectrum.
The polymer is realized with controllable reaction, low processing cost, good toughness and impact resistance, while reducing the glass transition temperature and processing temperature, improving the processing performance.
Smart Images

Figure CN119684554A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical materials, and specifically provides a thermoplastic optical material polymer and a preparation method and application thereof. Background Art
[0002] Polyurethane is a common optical material. Traditional polyurethane resins are mainly thermosetting resins. Thermosetting resins have problems such as long production cycles and high energy consumption, which leads to higher costs for producing thermosetting resins compared to thermoplastic resins. At the same time, some polyurethane resin materials have poor toughness and are prone to decomposition during processing.
[0003] Patent CN106471029B introduces a thiocarbamate urea thermoplastic optical resin. The resin uses mercaptan, isocyanate and amine substances, and can achieve thermoplasticity. However, the resin uses amine substances as monomers. Amine substances react violently with isocyanate, which will release a lot of heat, making the reaction difficult to control. Amine substances can catalyze the rapid reaction of mercaptan and isocyanate, which will make the reaction uncontrollable, resulting in uneven polymers. At the same time, amines and isocyanates form a urea structure with extremely high polarity, which is difficult to process and melt at a lower temperature.
[0004] Patent CN105960425B introduces a polythiourethane optical material polymer of polyisocyanate and polythiol, which is mainly used for lenses and eyeglasses. Considering that the carbon-sulfur bond is weak when thiol is combined with isocyanate and is easily broken by heating, the patent uses a thermosetting resin, which is inconvenient for production and processing. In addition, the product of this process has a low Tg, and the high processing temperature during production by some domestic eyewear manufacturers may cause deformation during the production process.
[0005] Patent CN106471030B introduces an optical material of a thiocarbamate urea molded body for lenses. This material uses a thiol having more than three mercapto groups, which results in excessive crosslinking of the system, making it impossible to perform thermoplastic processing. Summary of the invention
[0006] In order to solve the problems of uncontrollable reaction, poor processability, easy decomposition of polymers during processing, poor toughness of products, etc. in the prior art when preparing polyurethane optical materials, the present invention provides a thermoplastic optical material polymer, which can be processed by injection molding and has the advantages of controllable reaction and low processing cost. The optical material polymer prepared by the present invention not only has good toughness and impact resistance, but also has a low glass transition temperature and processing temperature, so that it has good processing performance while ensuring that the refractive index meets the quality standards.
[0007] Traditional optical materials are mainly based on thermosetting resins, which have problems such as long production cycle and high energy consumption. This leads to higher production costs compared to thermoplastic resins.
[0008] The invention provides a thermoplastic optical material polymer, which is obtained by mixing specific isocyanate and sulfur-containing compounds and adding hydroxyl monomers in a certain proportion and then curing through a polymerization reaction. The obtained product has a low glass transition temperature and processing temperature and good processing performance, and also has good toughness and impact resistance.
[0009] The thermoplastic optical material polymer contains a type I structure and a type II structure, the type I structure is shown in formula 1, and the type II structure is shown in formula 2:
[0010]
[0011] Among them, the type I structure includes the structure in which the isocyanate group is connected to the O element, which is -CH2-O-CO-NH-;
[0012] The type II structure includes the chemical structure of the isocyanate group connected to the S element, which is -CH2-S-CO-NH-.
[0013] Wherein, the CH bond directly connected to the oxygen atom connected to the isocyanate group in the type I structure has a peak position in the hydrogen nuclear magnetic resonance spectrum at 4.0ppm-4.5ppm.
[0014] The CH bond directly connected to the sulfur atom connected to the isocyanate group in the type II structure has a peak position at 2.9 ppm-3.4 ppm in the hydrogen nuclear magnetic resonance spectrum.
[0015] The peak area ratio of the nuclear magnetic resonance hydrogen spectrum of the type I structure and the type II structure is 0.03-0.15.
[0016] The present invention further provides a method for preparing the thermoplastic optical material polymer, which is prepared by curing isocyanate, sulfur-containing compounds and hydroxyl monomers, wherein the hydroxyl monomers include one or more of monothiol monohydroxy compounds and polyols.
[0017] More specifically, the preparation method of the thermoplastic optical material polymer comprises the following steps:
[0018] 1) Raw material pretreatment: The isocyanate, sulfur-containing compound, and hydroxyl monomer are separately placed in a container, heated to 60-80° C., and the container is evacuated to negative pressure for 1-3 hours;
[0019] After the raw materials are individually subjected to the above pretreatment, the water content of each raw material can be reduced to below 100 ppm.
[0020] 2) preparing a composition: mixing the raw materials obtained in step 1) and adding a catalyst accounting for 0.1-1 wt% of the total raw materials, mixing evenly to obtain a composition; the catalyst is one or more of dibutyltin dichloride, dibutyltin dilaurate, and stannous octoate.
[0021] Preferably, in step 2), antioxidants, release agents, UV powders, and dyes may be added to the composition as auxiliary agents according to actual needs to prevent oxidation, help demolding, receive light of a specific wavelength, adjust colors, etc., so as to adapt to different application environments. The auxiliary agents have been widely disclosed in the prior art in this field, and those used in this application are also in the prior art, and the inventors will not elaborate on them here.
[0022] 3) Prepolymerization of the composition: The composition obtained in step 2) is prepolymerized at 25-30° C. A vacuum pump is used for degassing during the prepolymerization process, and the vacuum degree is -0.08 to -0.1 MPa. The prepolymerization time is 0.5 to 2 hours to obtain a prepolymerized product;
[0023] The temperature of the feed liquid needs to be controlled during the prepolymerization process because heat will be released during the prepolymerization process. When the amount of feed liquid is large, excessive heat will be released, resulting in a rapid reaction in the prepolymerization stage. Therefore, human intervention is required to stabilize the temperature within the above range.
[0024] 4) Preparation of polymer: Curing the prepolymer product obtained in step 3) at 130-150° C. for 12-24 hours to obtain a thermoplastic optical material polymer.
[0025] Among the above-mentioned alternative raw materials, the preferred isocyanate is a diisocyanate, more specifically selected from 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate methyl ester, m-xylylene diisocyanate, 1,5-pentamethylene diisocyanate, allophanate-modified 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate, naphthalene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, biphenyl diisocyanate, 4,4-diphenylmethane diisocyanate, cyanate, 2,4'-diphenylmethane diisocyanate, 3,4-bis(isocyanatomethyl)tetrahydrothiophene, 2,5-diisocyanato-1,4-dithiane, 2,5-bis(isocyanatomethyl)-1,4-dithiane, 4,5-diisocyanato-1,3-dithiolane, 4,5-bis(isocyanatomethyl)-1,3-dithiolane, 2,2-diphenylmethane diisocyanate isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, 4,4-methylenediamine 2,5-bis(isocyanatomethyl)bicyclo[2.2.1]heptane, 2,6-bis(isocyanatomethyl)bicyclo[2.2.1]heptane, 3,8-bis(isocyanatomethyl)tricyclodecane, 3,9-bis(isocyanatomethyl)tricyclodecane, bis(isocyanatomethyl)naphthalene, bis(isocyanatomethyl)sulfide, bis(isocyanatoethyl)sulfide, bis(isocyanatomethyl)disulfide, bis(isocyanatoethyl)disulfide, bis(isocyanatomethylthio)methane , bis(isocyanateethylthio)methane, bis(isocyanatemethylthio)ethane, bis(isocyanateethylthio)ethane, 4,8-bis(isocyanatemethyl)tricyclodecane, 4,9-bis(isocyanatemethyl)tricyclodecane, 2,5-diisocyanatethiophene, 2,5-bis(isocyanatemethyl)thiophene, 2,5-diisocyanatetetrahydrothiophene, 2,5-bis(isocyanatemethyl)tetrahydrothiophene, dicyclohexylmethane diisocyanate, meta-xylyl diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane.
[0026] Preferably, the sulfur-containing compound contains two thiol groups, specifically selected from methanethiol, 1,2-ethanethiol, 1,2-propanethiol, 1,3-propanethiol, 1,4-butanethiol, 1,5-pentanethiol, 1,6-hexanethiol, 1,2-cyclohexanedithiol, 3,4-dimethoxybutane-1,2-thiol, 2-methylcyclohexane-2,3-thiol, 1,2-dimercaptopropyl methyl ether, 2,3-dimercaptopropyl methyl ether, bis(2-mercaptoethyl) ether, bis(mercaptomethyl) sulfide, bis(mercaptomethyl) disulfide, bis(mercaptoethyl) sulfide, bis(mercaptoethyl) disulfide, bis(mercaptomethylthio)methane, bis(2-mercaptoethylthio)methane, 1,2-bis(mercaptomethylthio)ethane, 1,2-bis(2-mercaptoethylthio) )ethane, 1,3-bis(mercaptomethylthio)propane, 1,3-bis(2-mercaptoethylthio)propane, 4,6-bis(mercaptomethylthio)-1,3-dithiane, 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithiacyclobutane, 2,5-dimercapto-1,4-dithiane, 2,5-dimethylthio-1,4-dithiane, ethylene glycol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(2-mercaptoacetate), diethylene glycol bis(3-mercaptopropionate), 1,4-cyclohexanediol bis(2-mercaptoacetate), 1,4-cyclohexanediol bis(3-mercaptopropionate), 3,3'-[1,2-ethylenedi(thio)]di-1-propanol, and thiodiglycol bis(mercapto)
[0027] Preferably, the monomercapto monohydroxy compound is selected from one or more of 2-mercaptoethanol, 2-(2-mercaptoethylthio)ethanol, 2-thiolethanol, 2-(2-mercaptoethoxy)ethanol, 2-mercaptopropanol, 1-mercapto-2-propanol, 3-mercapto-1-propanol, and mercaptohexanol; the polyol is selected from diols, including ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, dipropylene glycol, neopentyl glycol, 3-methyl-1,5-pentanediol, methylpropylene glycol, 1,4-dithiane-2,5-diol, 2,5-bis(hydroxymethyl)-1,4-dithiane, and bis(hydroxyethyl)sulfide.
[0028] In order to achieve the thermoplastic effect, the above-mentioned monomers are all difunctional monomers, so that the obtained materials have a linear structure. If other non-difunctional monomers are used, the chains will be cross-linked with each other, resulting in a significant increase in processing temperature and inability to perform thermoplastic processing.
[0029] Adding mercapto monomers can improve the performance of polymers. By introducing hydroxyl-containing monomers into the raw monomers, their "-O-CO-NH-" has a higher bond energy than "-S-CO-NH-" and is not easy to break. Therefore, the thermoplastic optical material polymer finally obtained contains type I structure and type II structure, which significantly improves the problem of thermal decomposition, reduces the processing temperature and glass transition temperature, and inhibits thermal decomposition during processing.
[0030] In the composition of the optical material polymer of the present invention, the ratio of the sulfur-containing compound to the hydroxyl monomer to the isocyanate should be calculated from their main functional groups, that is, the ratio of the sulfur-containing compound to the hydroxyl monomer to the isocyanate is converted from the ratio of the amount of the thiol, hydroxyl and isocyanate functional groups. Therefore, the molar ratio of the sum of the thiol of the sulfur-containing compound, the thiol of the monothiol monohydroxy compound, the hydroxyl of the monothiol monohydroxy compound, and the hydroxyl of the polyol to the isocyanate group of the isocyanate is preferably 1:1.
[0031] The present invention also provides an optical lens, which is obtained by thermoplastic processing of the thermoplastic optical material polymer obtained above, wherein the thermoplastic processing is injection molding or compression molding, and annealing is performed at 90-120° C. for 1-8 hours after the thermoplastic processing.
[0032] After thermoplastic processing, the molecular weight of the polymer may decrease due to depolymerization, and annealing is required to restore the molecular weight.
[0033] The thermoplastic optical material polymer and its preparation method and application provided by the present invention have achieved the following technical effects:
[0034] The thermoplastic optical material polymer has simple synthesis and processing technology, maintains a high refractive index and Abbe number, and can be thermoplastic processed; the polymer is achieved by using key monomers binary sulfur-containing compounds and diisocyanate polymerization, and can reach a refractive index of more than 1.5950, but due to the weak -S-CO-NH- bond energy, when subjected to high-temperature processing above 180°C, the product will be severely degraded, resulting in the inability of related products to be used in practice; therefore, the inventors finally introduced a small amount of -O-CO-NH- groups with stronger bond energy, which did not affect the refractive index while effectively improving the high-temperature processing stability and impact resistance of the material.
[0035] Furthermore, the glass transition temperature (Tg), refractive index, molecular weight, impact performance and processing temperature of the product are finally monitored, and should meet the requirements of Tg ≥ 110 ° C, refractive index ≥ 1.5950, and impact strength ≥ 4.50KJ / m 2 , processing temperature ≤200℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1The nuclear magnetic resonance hydrogen spectrum of the thermoplastic optical material polymer prepared in Example 1;
[0037] Figure 2 The nuclear magnetic resonance hydrogen spectrum of the thermoplastic optical material polymer prepared in Example 2;
[0038] Figure 3 The nuclear magnetic resonance hydrogen spectrum of the thermoplastic optical material polymer prepared in Example 3;
[0039] Figure 4 The hydrogen nuclear magnetic resonance spectrum of the thermoplastic optical material polymer prepared in Example 4;
[0040] Figure 5 The hydrogen nuclear magnetic resonance spectrum of the thermoplastic optical material polymer prepared in Example 5;
[0041] Figure 6 The nuclear magnetic resonance hydrogen spectrum of the thermoplastic optical material polymer prepared in Comparative Example 1;
[0042] Figure 7 The nuclear magnetic resonance hydrogen spectrum of the thermoplastic optical material polymer prepared in Comparative Example 2;
[0043] Figure 8 The nuclear magnetic resonance hydrogen spectrum of the thermoplastic optical material polymer prepared in Comparative Example 3;
[0044] Fig. 9 This is the hydrogen nuclear magnetic resonance spectrum of the thermoplastic optical material polymer prepared in Comparative Example 4. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.
[0046] The substances and reagents used in the examples of the present invention are generally available on the market unless otherwise specified. The following examples are mainly described using the following substances as examples:
[0047] Sulfur-containing compound: 2,5-dimethylmercapto-1,4-dithiane (hereinafter referred to as BMMD).
[0048] Hydroxyl monomer: 2-mercaptoethanol; ethylene glycol.
[0049] Isocyanate: dicyclohexylmethane diisocyanate (hereinafter referred to as HMDI).
[0050] Catalyst: dibutyltin dichloride.
[0051] The thermoplastic optical material polymer proposed in the present invention achieves thermoplasticity through monomer selection. Therefore, the preparation steps of the present invention embodiment and the comparative example are the same, and only the monomers and proportions are different.
[0052] Except that the polymer of Comparative Example 1 contains only the Type II structure, the polymers obtained in other Examples and Comparative Examples contain both the Type I structure and the Type II structure, the Type I structure is shown in Formula 1, and the Type II structure is shown in Formula 2:
[0053]
[0054] Among them, the type I structure is a structure in which an isocyanate group is connected to an O element, which is -CH2-O-CO-NH-;
[0055] The type II structure is a chemical structure in which an isocyanate group is connected to an S element, which is -CH2-S-CO-NH-.
[0056] The raw material proportions of Examples 1-5 and Comparative Examples 1-4 are shown in Table 1.
[0057] Table 1 Ratio of raw material components in Examples 1-5 and Comparative Examples 1-4 and ratio of type I structure and type II structure in the product optical material polymer
[0058] serial number BMMD 2-Mercaptoethanol Ethylene glycol HMDI Class I structure / Class II structure Example 1 42.82% 0.98% 0.00% 56.20% 0.0301 Example 2 42.55% 0.00% 0.98% 56.47% 0.0741 Example 3 41.14% 1.84% 0.00% 57.02% 0.0573 Example 4 40.92% 0.91% 0.91% 57.26% 0.0989 Example 5 40.50% 0.00% 1.90% 57.60% 0.1507 Comparative Example 1 44.73% 0.00% 0.00% 55.27% 0.0000 Comparative Example 2 35.83% 0.00% 4.00% 60.17% 0.3586 Comparative Example 3 35.34% 4.81% 0.00% 59.85% 0.1562 Comparative Example 4 36.26% 2.03% 2.03% 59.68% 0.2378
[0059] Examples 1-5 and Comparative Examples 1-4 adopt the same preparation method, and the specific steps are as follows:
[0060] 1) Raw material pretreatment: BMMD, HMDI and hydroxyl monomer (2-mercaptoethanol and / or ethylene glycol, wherein no hydroxyl monomer is added in Comparative Example 1) are separately placed in containers, heated in a water bath at 80° C., and evacuated to negative pressure by a vacuum pump. This process lasts for 2 hours, and its main function is to remove moisture from the monomers;
[0061] 2) Preparing the composition: weigh the corresponding amount of monomers according to the ratio shown in the above table. The monomers do not need to be added in order. Add dibutyltin dichloride catalyst to the final composition. The amount of catalyst added is 0.6wt% of the mass of the composition;
[0062] 3) Prepolymerization of the composition: The composition is temperature controlled at 25° C. and pumped to negative pressure by a vacuum pump, with the vacuum degree controlled at -0.08 to -0.1 MPa. The process is continued for 1 hour to obtain a prepolymerized product, and the water in the system is further removed;
[0063] 4) Polymer preparation: The prepolymer product was placed in an oven and cured at 130° C. for 12 h to obtain a thermoplastic optical material polymer.
[0064] The hydrogen nuclear magnetic resonance spectra of the polymers obtained in Examples 1-5 and Comparative Examples 1-4 are shown in Figures 1 to 9 , wherein the peak position of the hydrogen nuclear magnetic resonance spectrum of the CH bond directly connected to the oxygen atom connected to the isocyanate group in the type I structure is at 4.0ppm-4.5ppm;
[0065] The peak position of the hydrogen nuclear magnetic resonance spectrum of the CH bond directly connected to the sulfur atom connected to the isocyanate group in the type II structure is at 2.9ppm-3.4ppm.
[0066] The nuclear magnetic resonance hydrogen spectrum peak area ratios of the type I structure and the type II structure in the polymers obtained in Examples 1-5 and Comparative Examples 1-4 are shown in Table 1. The main difference between Examples 1-5 and Comparative Examples 2-4 is that the peak area ratios of the type I structure / type II structure are different, that is, the ratios of the type I structure / type II structure are different. The comparison of the ratios is shown below:
[0067] Example 1<Example 3<Example 2<Example 4<Example 5<Comparative Example 3<Comparative Example 4<Comparative Example 2.
[0068] Comparative Example 1 shown in Table 1 is a case where no hydroxyl monomer is added, so the ratio of the two structures in Comparative Example 1 is 0. Comparative Examples 2, 3, and 4 have an obviously excessive hydroxyl content, so the ratio of the two structures in Comparative Examples 2, 3, and 4 is relatively high.
[0069] Experimental example
[0070] The polymers obtained in the above Examples 1-5 and Comparative Examples 1-4 were tested for their properties, and the specific testing methods are as follows.
[0071] 1. Tg test: that is, glass transition temperature test. After curing, take 3-5 mg of sample and test it using differential scanning calorimeter. Test standard: ISO 11357.2 (0-200℃, 20℃ / min, take the result of the second heating).
[0072] 2. Refractive index: Make the sample into small square pieces and use Abbe refractometer for testing. Testing standard: ASTM D542.
[0073] 3. Molecular weight: In the present invention, molecular weight indicates the degree of curing of the composition and the degree of decomposition after injection molding. A 5-7 mg sample is taken and tested by gel permeation chromatography. Testing standard: ISO 16014-4:2019.
[0074] 4. Impact performance: The present invention uses impact performance to indicate the toughness of the sample, and uses a cantilever beam impact tester for testing. Testing standard: GB / T 21189-2007
[0075] 5. Processing temperature: The processing temperature is to heat the sample to a temperature with a certain fluidity. The processing temperature shown in the present invention is the lowest temperature for injection molding. The injection molding machine is a plastic injection molding machine of Ningbo Changfeiya Plastic Machinery Manufacturing Co., Ltd., and its model is VE1200Ⅲ-210; the back pressure is uniformly 5.50Mpa, the injection pressure is 125Mpa, and the injection speed is 90mm / s; the extruder screw temperature is set to 6 sections, and multiple groups of temperatures are used for processing tests. The material is directly added to the injection molding machine. When the set temperature can just produce uniform material from the nozzle, the highest temperature among the 6 sections is taken as the processing temperature. If the material is uneven, the material produced from the nozzle has obvious granularity.
[0076] The test results are shown in Table 2.
[0077] Table 2 Performance test results of Examples 1-5 and Comparative Examples 1-4
[0078]
[0079]
[0080] Observe the data in Table 2:
[0081] 1. As the hydroxyl content in the hydroxyl monomer increases, the ratio of type I structure / type II structure increases, and Tg begins to show a downward trend. At the same time, this also improves the processing performance of the material under certain conditions; in the processing temperature column, the processing temperature decreases as the hydroxyl content increases.
[0082] 2. The refractive index shows a downward trend as the ratio of Type I structure / Type II structure increases. In the examples, although the refractive index decreases to a certain extent, the decrease in the refractive index is still within an acceptable range because the proportion of added hydroxyl groups is relatively small. In Comparative Examples 2-4, the hydroxyl content is greatly increased, which makes the ratio of Type I structure / Type II structure too high, resulting in a significant decrease in the refractive index. Therefore, it is necessary to control the hydroxyl content in the system and not to make it too high.
[0083] 3. The impact after processing reflects the toughness of the material to a certain extent, and the impact performance increases with the increase of the ratio of Type I structure / Type II structure.
[0084] 4. As a polyester material, the present invention has a certain degree of decomposition during the processing. Adding hydroxyl groups can alleviate this problem to a certain extent. After processing, the molecular weight increases with the increase of the ratio of type I structure / type II structure. At the same time, the reduction of Tg after processing is compared. The reduction of Tg after processing improves with the increase of the ratio of type I structure / type II structure. However, Tg less than 110°C will have an adverse effect on the subsequent processing technology that may be carried out (such as hard coating). Therefore, although the Tg reduction of comparative examples 2-4 is small, it is still not suitable for subsequent processing. Therefore, adding hydroxyl monomers to the system can improve the decomposition problem, but adding too much will result in too low Tg.
[0085] 5. The Tg of Comparative Examples 2-4 after processing is relatively low, because the ratio of Type I structure / Type II structure is too high, resulting in a low Tg.
[0086] Therefore, as a thermoplastic optical material, the present invention needs to add an appropriate amount of hydroxyl monomer (such as ethylene glycol, 2-mercaptoethanol) to the system to control the ratio of type I structure / type II structure, so as to achieve a certain processability and toughness, while also having a certain anti-decomposition ability, and Tg and refractive index are not significantly affected.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A thermoplastic optical material polymer, comprising a type I structure and a type II structure, wherein the type I structure is -CH2-O-CO-NH-, and the type II structure is -CH2-S-CO-NH-, characterized in that: The nuclear magnetic resonance hydrogen spectrum peak area ratio of the type I structure to the type II structure is 0.03-0.
15.
2. The thermoplastic optical material polymer according to claim 1, characterized in that The peak position of the type I structure in the nuclear magnetic resonance hydrogen spectrum is 4.0-4.5 ppm, and the peak position of the type II structure in the nuclear magnetic resonance hydrogen spectrum is 2.8-3.4 ppm.
3. A method for preparing the thermoplastic optical material polymer according to claim 1, characterized in that: The invention is prepared by curing isocyanate, sulfur-containing compound and hydroxyl monomer, wherein the hydroxyl monomer comprises one or more of monomercapto monohydroxyl compound and polyol.
4. The method for preparing a thermoplastic optical material polymer according to claim 3, characterized in that: The specific steps are as follows: 1) Raw material pretreatment: All raw materials are placed in containers separately, heated to 60-80°C, and the container is pumped to negative pressure for 1-3 hours; 2) preparing a composition: mixing the raw materials obtained in step 1) and adding a catalyst accounting for 0.1-1 wt% of the total raw materials, and mixing them evenly to obtain a composition, wherein the catalyst is one or more of dibutyltin dichloride, dibutyltin dilaurate, and stannous octoate; 3) Prepolymerization of the composition: The composition obtained in step 2) is prepolymerized at 25-30° C. A vacuum pump is used for degassing during the prepolymerization process. The vacuum degree of degassing is -0.08 to -0.1 MPa. The prepolymerization time is 0.5 to 2 hours to obtain a prepolymerized product; 4) Preparation of polymer: Curing the prepolymerized product in step 3) at 130-150° C. for 12-24 hours to obtain a thermoplastic optical material polymer.
5. The method for preparing a thermoplastic optical material polymer according to claim 3, characterized in that: The isocyanate is a diisocyanate selected from 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate methyl ester, m-xylylene diisocyanate, 1,5-pentamethylene diisocyanate, allophanate modified 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate, naphthalene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, biphenyl diisocyanate, 4,4-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, methane diisocyanate, 3,4-bis(isocyanatomethyl)tetrahydrothiophene, 2,5-diisocyanato-1,4-dithiane, 2,5-bis(isocyanatomethyl)-1,4-dithiane, 4,5-diisocyanato-1,3-dithiolane, 4,5-bis(isocyanatomethyl)-1,3-dithiolane, 2,2-diphenylmethane diisocyanate isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, 4,4-methylene-bis(cyclohexyl) isocyanate), methylcyclohexane diisocyanate, 2,5-bis(isocyanatemethyl)bicyclo[2.2.1]heptane, 2,6-bis(isocyanatemethyl)bicyclo[2.2.1]heptane, 3,8-bis(isocyanatemethyl)tricyclodecane, 3,9-bis(isocyanatemethyl)tricyclodecane, bis(isocyanatemethyl)naphthalene, bis(isocyanatemethyl)sulfide, bis(isocyanateethyl)sulfide, bis(isocyanatemethyl)disulfide, bis(isocyanateethyl)disulfide, bis(isocyanatemethylthio)methane, bis(isocyanatemethyl)sulfide One or more of bis(isocyanatoethylthio)methane, bis(isocyanatomethylthio)ethane, bis(isocyanatoethylthio)ethane, 4,8-bis(isocyanatomethyl)tricyclodecane, 4,9-bis(isocyanatomethyl)tricyclodecane, 2,5-diisocyanatothiophene, 2,5-bis(isocyanatomethyl)thiophene, 2,5-diisocyanatotetrahydrothiophene, 2,5-bis(isocyanatomethyl)tetrahydrothiophene, dicyclohexylmethane diisocyanate, meta-xylyl diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane.
6. The method for preparing a thermoplastic optical material polymer according to claim 3, characterized in that: The sulfur-containing compound contains two mercapto groups and is selected from methanedithiol, 1,2-ethanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,2-cyclohexanedithiol, 3,4-dimethoxybutane-1,2-dithiol, 2-methylcyclohexane-2,3-dithiol, 1,2-dimercaptopropyl methyl ether, 2,3-dimercaptopropyl methyl ether, bis(2-mercaptoethyl) ether, bis(mercaptomethyl) sulfide, bis(mercaptomethyl) disulfide, bis(mercaptoethyl) sulfide, bis(mercaptoethyl) disulfide, bis(mercaptomethylthio)methane, bis(2-mercaptoethylthio)methane, 1,2-bis(mercaptomethylthio)ethane, 1,2-bis(2-mercaptoethylthio)ethane one or more of alkane, 1,3-bis(mercaptomethylthio)propane, 1,3-bis(2-mercaptoethylthio)propane, 4,6-bis(mercaptomethylthio)-1,3-dithiane, 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithiacyclobutane, 2,5-dimercapto-1,4-dithiane, 2,5-dimethylthio-1,4-dithiane, ethylene glycol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(2-mercaptoacetate), diethylene glycol bis(3-mercaptopropionate), 1,4-cyclohexanediol bis(2-mercaptoacetate), 1,4-cyclohexanediol bis(3-mercaptopropionate), 3,3'-[1,2-ethylenedi(thio)]di-1-propanol, and thiodiglycol mercaptan.
7. The method for preparing a thermoplastic optical material polymer according to claim 3, characterized in that: The monomercapto monohydroxy compound is selected from one or more of 2-mercaptoethanol, 2-(2-mercaptoethylthio)ethanol, 2-mercaptoethanol, 2-(2-mercaptoethoxy)ethanol, 2-mercaptopropanol, 1-mercapto-2-propanol, 3-mercapto-1-propanol, and mercaptohexanol; The polyol is a diol, selected from one or more of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, dipropylene glycol, neopentyl glycol, 3-methyl-1,5-pentanediol, methylpropylene glycol, 1,4-dithiane-2,5-diol, 2,5-bis(hydroxymethyl)-1,4-dithiane, and bis(hydroxyethyl) sulfide.
8. An optical lens, obtained by injection molding or compression molding of the thermoplastic optical material polymer according to claim 1.
Citation Information
Patent Citations
Polymer compositions for optical materials and optical materials
CN105960425B
Polymer compositions for optical materials and their uses
CN106471029B
Polymer compositions for optical materials and their uses
CN106471030B